French wh in-situ - Lena Baunaz; Giuliano Bocci; Ur Shlonsky (Isogloss)
This paper investigates the acceptability of wh in-situ expressions in embedded contexts in French. We report on two experiments that tested the acceptability of wh in-situ and ex-situ in embedded clauses of biclausal direct wh-questions and in indirect questions, and how their acceptability is modulated by the presence of the negation in the embedded clause. In Experiment 1, the contexts favored a D-linked interpretation of the wh-element (in the sense of Pesetsky 1987), while the contexts in Experiment 2 disfavored it. Our results show that the in-situ strategy is generally more acceptable (or at least equally acceptable) than the ex-situ strategy in direct questions with long construal, regardless of D-linking and negation. By contrast, the in-situ strategy is significantly less acceptable than the ex-situ one in indirect questions, regardless of D-linking and negation. Our findings indicate that in long construal direct wh-questions, negation fails to selectively block wh in-situ. In this respect, French differs from many other languages (see e.g., Beck & Kim 1997, a.o.). We show that D-linking is not a necessary condition for in-situ in French. We discuss how our findings relate to the current debate between alternative formal analyses of wh in-situ in French.